2019
DOI: 10.21776/ub.jpal.2019.010.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Analysis on Tertiary Channels Using Macroinvertebrate In Songka Sub-District, Palopo City

Abstract: Changes in the condition of aquatic environment are now a major problem for the survival of every organism caused by changes in land use, human activities, and agriculture. This study aims to determine the structure of macroinvertebrate communities. In addition, this study also aims to conduct analysis on BMWP index and water quality testing using physical and chemical parameters. This study was conducted on tertiary channels in Songka Sub-District, Palopo City. Each station's data collection covered relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…The visible difference in the value of these could be due to the increase in anthropogenic activities around and directly on the water body as human activities such as agriculture and mining have been on the increase (Liu et al, 2022). The low water temperature recorded at the various sampled stations could be due to the period of sampling, which was early hours of the day (Rais et al, 2019). The ideal range of temperature for most aquatic organisms, macroinvertebrates inclusive, ranges from 26°C to 32°C (Orozco-González and Ocasio-Torres, 2023).…”
Section: Physicochemical Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The visible difference in the value of these could be due to the increase in anthropogenic activities around and directly on the water body as human activities such as agriculture and mining have been on the increase (Liu et al, 2022). The low water temperature recorded at the various sampled stations could be due to the period of sampling, which was early hours of the day (Rais et al, 2019). The ideal range of temperature for most aquatic organisms, macroinvertebrates inclusive, ranges from 26°C to 32°C (Orozco-González and Ocasio-Torres, 2023).…”
Section: Physicochemical Variablesmentioning
confidence: 99%
“…Rais et al (2019) reported that low temperatures affect low values of BOD, which in turn lead to an increase in DO. Also, water ow speed from a body of water can help in macroinvertebrates' distribution as high ow rate tends to wash them from their supportive substrate(Mamun et al., 2022; Anh et al, 2023).…”
mentioning
confidence: 99%
“…The water temperature conditions in the two rivers, although there is no significant difference, can be seen to be lower in the upstream part of the river. This is due to the influence of vegetation cover on the river body because, at the upstream station, there is still a lot of forest vegetation (Fierro et al 2017;Rais et al 2019). The optimal temperature range for the life of aquatic organisms, including macroinvertebrates, ranges from 26°C to 32°C (Orozco-González and Ocasio-Torres 2023).…”
Section: Physical and Chemical Parameters Of River Water Qualitymentioning
confidence: 99%
“…The optimal temperature range for the life of aquatic organisms, including macroinvertebrates, ranges from 26°C to 32°C (Orozco-González and Ocasio-Torres 2023). In the Watumokala River, there is a tendency for low temperatures to affect low TDS and BOD values causing high DO (Rais et al 2019). Meanwhile, the Nokambu River shows high water temperature due to a lack of vegetation cover so it is also in line with the increase in water flow rate which causes an increase in the values of TSS, TDS and BOD, and COD (Labajo-Villantes and Nuñeza 2015).…”
Section: Physical and Chemical Parameters Of River Water Qualitymentioning
confidence: 99%
“…Segmen hilir sungai menunjukkan kondisi tercemar ringan hingga tercemar berat. Metrik BMWP-ASPT telah digunakan pula untuk mengevaluasi kualitas perairan sungai diantaranya oleh Handayani et al (2001), Rahman (2017), Rais et al (2019), Dewi & Wardhana (2020), dan Tawati et al (2020.…”
Section: Bmwp-asptunclassified